Oxidation of sputtered W-based coatings - Cavaleiro, A. (2000)
In this paper, a review of the influence of the addition of different chemical elements to some transition metal nitrides and carbides on their oxidation behaviour will be presented. The role of the addition of [`]reactive elements' (RE) on the type of oxide phases formed, on the morphology of the oxide layers, on the oxidation kinetics and on the oxidation rate is emphasized. Examples of the system W-N/C when Ti, Ni and Si are added, will be shown. The beneficial action of the additional element on oxidation resistance can be due either to the formation of some type of protective oxide layer, apart from the typical oxides formed for those metal compounds, or to the blocking effect to the elemental diffusion, which is due to some type of compound precipitation in the diffusion paths.